GAMBARAN PENGETAHUAN DAN SIKAP MASYARAKAT TENTANG PEMAKAIAN GIGI TIRUAN DI DESA MAYANG PONGKAI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Yeyen Gumayesty (Sistem Informasi, 2017)
Denture is a removable dental prosthesis which replaces the masticatory surface and accompanying structures of an upper arch and lower jaw. The function of dentures is the esthetic function recovery, which still lags tissue preservation, prevention of migration of teeth, chewing load distribution improvement. Denture should be kept clean to prevent further tooth loss, gingival inflammation or infection of bacteria and fungi and prevents the denture does not smell.The aim of research to describe the behavior of the public about the use of denture in Mayang Pongkai Village. Type a descriptive quantitative research. The population is the entire community of Mayang Pongkai Village Central Kampar Kiri with population 2663 people with a sample of 96 respondents. Sampling technique using stratified sampling. Analysis of the data used to describe the univariate independent and dependent variables are presented in the form of a frequency distribution. The research result most respondents did not wear a denture that is 70 respondents (72.9%), most of the respondents had a good knowledge ie 19 respondents (73.1%) and the majority of respondents have a negative attitude were 19 respondents (73%). Suggestions research is expected to generate awareness for the community to create dentures to dental health professionals are dentists who have partnered with dental techniques. Local health workers to conduct counseling on the risks of making dentures in non-health personnel and strive provide affordable dental care to the community.